The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/dom.13813
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intentional weight loss on diabetic kidney disease

Abstract: Type 2 diabetes mellitus (T2DM) and obesity constitute interwoven pandemics challenging healthcare systems in developed countries, where diabetic kidney disease (DKD) is the most common cause of end‐stage renal disease. Obesity accelerates renal functional decline in people with T2DM. Intentional weight loss (IWL) strategies in this population hold promise as a means of arresting DKD progression. In the present paper, we summarize the impact of IWL strategies (stratified by lifestyle intervention, medications,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…New therapies which improve outcomes for people with type 2 diabetes and more advanced CKD are required. Intentional weight loss strategies, including metabolic surgery, and mesenchymal stem cells hold promise in this regard 6,7,33 . Integrated diabetes and nephrology care at later CKD stages may also improve patient outcomes, particularly for people with diabetes and additional CKD aetiologies 5 , and should be considered to lower cardiovascular and renal risk in those with higher sTNFR1 values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…New therapies which improve outcomes for people with type 2 diabetes and more advanced CKD are required. Intentional weight loss strategies, including metabolic surgery, and mesenchymal stem cells hold promise in this regard 6,7,33 . Integrated diabetes and nephrology care at later CKD stages may also improve patient outcomes, particularly for people with diabetes and additional CKD aetiologies 5 , and should be considered to lower cardiovascular and renal risk in those with higher sTNFR1 values.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced integration of diabetes and nephrology care, including earlier referral to nephrology services, can improve renal outcomes for people with diabetes and chronic kidney disease (CKD) 5 . Intentional weight loss strategies, including metabolic surgery, may also reduce the burden of cardiovascular disease and slow renal functional decline in people with type 2 diabetes and CKD [6][7][8] . Given the range of new and efficacious options for the treatment of diabetes and its complications, identifying subgroups at the highest risk of rapid renal functional decline and/or death will help clinicians to appropriately stratify intensification of therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic surgery achieves sustained weight loss and substantially lowers mortality in people with obesity ( 57 , 58 ). Obesity is increasingly recognised as an important driver of CKD progression and is an important barrier to kidney transplantation, yet obesity is not specifically addressed during routine management of CKD and ESKD despite evidence of benefit ( 59 ). We herein summarise evidence supporting the potentially diverse roles of metabolic surgery in slowing DKD and CKD progression, as well as facilitating access to kidney transplantation and management of post-transplant metabolic complications.…”
Section: Metabolic Surgery Rearranges the Gut To Effectively Treat Obmentioning
confidence: 99%
“…Large-scale observational studies have demonstrated that metabolic surgery reduces the incidence of albuminuria, slows progressive renal functional decline, and reduces the incidence of ESKD in patients with obesity [10][11][12][13]. Improved control of body weight, blood pressure, dyslipidaemia, and glycaemia contribute to these findings [14]. However, in patients with type 2 diabetes, the antiproteinuric effect of metabolic surgery occurs independently of improvements in body weight, blood pressure, and glycaemia [15].…”
Section: Introductionmentioning
confidence: 99%